The true statement about why the Fibonacci sequence is recursively defined is (c) The Fibonacci sequence is recursively-defined because you must know the values of the two previous terms in order to find the value of the next term
<h3>How to determine the true statement</h3>
With an exception to the first two terms, each term of the Fibonacci sequence is the sum of the two previous terms
This means that,
The Fibonacci sequence cannot be defined explicitly, because the two previous terms can not be determined by a direct formula
Hence, the true statement about why the Fibonacci sequence is recursively defined is (c)
Read more about the Fibonacci sequence at:
brainly.com/question/16934596
The ordered pairs of the solution to the system of equation are [(3, 6), (-3, 18)]
<h3>System of equations</h3>
Given the following system of equations expressed as:
f(x) = x² - 2x + 3 and f(x) = -2x + 12
Since they are both function of x, hence;
x² - 2x + 3 = -2x + 12
x² - 2x + 3 + 2x - 12 = 0
x² - 9 = 0
x² = 9
x = ±√9
x = ±3
If x = 3
f(x) = -2(3) + 12
f(x) = 6
If x = -3
f(x) = -2(-3) + 12
f(x) =18
Hence the ordered pairs of the solution to the system of equation are [(3, 6), (-3, 18)]
Learn more on system of equation here: brainly.com/question/14323743
#SPJ1
Answer:
the answer is 5/2 or alternative form 2*1/2 so the answer is C
A = 30
B = 41
C = 70
A < B + C
30 < 41+70 ==> 30 < 111 (TRUE)
B < A + C ==>
41 < 30 + 70 ==> 41 < 100 (TRUE)
C < A+B
70 < 30 + 41 ==> 70 < 71 (TRUE)
Yes, can!
F(x)= y
this is the equation that explains the problem<span />